The NG domain of the prokaryotic signal recognition particle receptor, FtsY, is fully functional when fused to an unrelated integral membrane polypeptide - Zelazny, Adrian (The National Academy of Sciences of the USA, 1997)
Recent studies have revealed that Escherichia coli possesses an essential targeting system for integral membrane proteins, similar to the mammalian signal recognition particle (SRP) machinery. One essential protein in this system is FtsY, a homologue of the α-subunit of the mammalian SRP-receptor (SR-α). However, E. coli does not possess a close homologue of the integral membrane protein SR-β, which anchors SR-α to the membrane. Moreover, although FtsY can be found as a peripheral membrane protein, the majority is found soluble in the cytoplasm. In this study, we obtained genetic and biochemical evidence that FtsY must be targeted to the membrane for proper function. We demonstrate that the essential membrane targeting activity of FtsY is mediated by a 198-residue-long acidic N-terminal domain. This domain can be functionally replaced by unrelated integral membrane polypeptides, thus avoiding the need for specific FtsY membrane targeting factors. Therefore, the N terminus of FtsY constitutes an independent domain, which is required only for the targeting of the C-terminal NG domain of FtsY to the membrane.